Russian healthcare system digitalization: Opportunities and contradictions - A. I. Afyan; D. V. Polozova; A. A. Gordeeva (Цифровое право, 2021)
The article is devoted to the opportunities and key contradictions of the Russian state healthcare system digitalization project implementation. The authors analyze various aspects of the system digitalization algorithms in light of the federal project “Creation of the Single Digital Circuit in Healthcare based on the Unified State Health Information System”. The aim of the article was to identify problems within goal-setting, documentation development, and practical implementation of the healthcare system digitalization project, as well as to come up with proposals for eliminating these issues. The analysis showed the inefficiency of the expensive healthcare system digitalization project, which has both objective and subjective reasons for its low effectiveness. The authors come to the conclusion that it is necessary to eliminate a number of contradictions and barriers in the framework of the project implementation in order to increase the efficiency of both the healthcare system itself and the high budget federal project of the economy digitalization as a whole. The practical significance of the article consists in the applicability of proposed approach to making the necessary amendments to the current federal project documentation, which will ensure a focus on real needs within the framework of the initiative implementation. The work may be of interest to civil servants, initiators of projects on the healthcare system digital transformation, governmental bodies, healthcare organizations managers, students, and practitioners.